Effects of calcium stearate and metal hydroxide additions on the irradiated LDPE/EVA compound properties - Sabet, M. (2013)
The effects of the addition different fillers, such as calcium stearate (CS), aluminum trihydrate (ATH), and magnesium hydroxide (MH), on the properties of lowdensity polyethylene/ethylene vinyl acetate (LDPE/EVA) compounds were studied. It was determined that the adhesion forces among MH and LDPE/EVA compounds were stronger than those among analogue compounds containing ATH in each irradiated sample. The gel content (GC) values of irradiated compounds containing ATH were higher than those of the analogue MH compounds, and CS addition enhanced the GC values of all compounds in each irradiated sample. The density values of compounds with MH content were higher than those of analogue compounds containing ATH in each irradiated sample. It was shown that all pristine compounds whose density was compared with irradiated samples had maximum values. Addition of CS and enhancing irradiation to polymer compounds reduced the density values. Compounds with high CS contents and were highly irradiated showed high tensile strength (TS) values. The TS values of compounds containing ATH were lower than those of analogue compounds containing MH in each irradiated sample. ATH or MH addition to polymer matrices reduced the elongation at break (EB) values in each irradiated sample. The EB values of compounds containing ATH were higher than those of compounds containing MH in each irradiation range. CS addition improved polymer chain flexibility and enhanced the compoundÅ EB values with irradiation.